THE ROLE OF ANTIBODIES TO ACETYLCHOLINE, MUSCLE-SPECIFIC KINASE, TITIN AND SOX1 RECEPTORS IN PREDICTING SEVERE MYASTHENIA GRAVIS - Kalbus, O.I.; Nefodov, O.O. (World of Medicine and Biology, 2022)
182 patients with myasthenia gravis aged 18 to 83 years were examined. The severity of myasthenia gravis was quantified on the Quantitative Myasthenia Gravis scale. An immunological test was performed to determine the presence and titer of antibodies to acetylcholine receptors, muscle-specific receptor tyrosine kinase, and to determine the presence of antibodies against titin and SOX1. Antibodies to acetylcholine receptors were detected in 124 (68.1 %) patients, including 108 (73.5 %) with generalized and 16 (45.7 %) with the ocular form of the disease. Antibodies to muscle-specific kinase were detected in 16 (10.9 %) patients with generalized myasthenia gravis. Titin antibodies were detected in 53 (29.1 %) patients with generalized myasthenia gravis. Antibodies to SOX1 have been diagnosed in 10 (6.8 %) subjects with a generalized form of myasthenia. The ability of these immunological markers to predict the development of severe myasthenia gravis was assessed by ROC analysis. It was found that the titer of antibodies to acetylcholine can be used to predict the severe course of myasthenia gravis. If the antibody titer level to acetylcholine is above 6.9 nmol/L, the ratio of chances of severe disease in patients with myasthenia gravis compared to patients with a lower level of titer of these antibodies is 22.35 (95.0 % CI 6.98–71.56), p
Keywords: myasthenia gravis; antibodies; titin; SOX1; muscle-specific kinase; acetylcholine receptors; prognosis; course